Analisis Struktur dan Fungsi Bahasa Suku Hubula Sebagai Bahasa Yang Sering Digunakan di Lembah Balim Papua: Analysis of The Structure and Function of Hubula Language as The Most Spoken Language in Balim Valley Papua - Grets Lewis Theodore Walilo (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The purpose of this study is to understand the structure and function of Hubula tribe language as the most spoken language Balim Valley Papua. Whereas the language has an easy sentence pattern to study. This researchwas conducted with a sociolinguistic approach that focused on the usage of language in the society to perform its function. The result showed that Hubula tribe language is understandable and spoken by the other five tribes in Balim Valley. By knowing some basic vocabularies, the sentence’s structure of Hubula tribe language can be learned easily. As the bridge for interaction, this language has several functions such as; personal function, informative function and interaction function.